Unraveling the Interplay between Financial Knowledge and FOMO in Shaping Adolescent Consumptive Behavior in Jakarta - Putri, Nisas Shofsofa Bilbina; Widyastuti, Umi; Mahfirah, Titis Fatarina (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study seeks to investigate the impact of two variables, namely financial knowledge and the Fear of Missing Out (FOMO), on the behavior of teenagers in Jakarta as consumers. Financial knowledge and FOMO are considered as exogenous variables, while consumer behavior is treated as the endogenous variable. A total of 160 samples were utilized for this research, employing purposive sampling as the data collection technique. The analysis method employed was the Partial Least Square - Structural Equation Model (PLS-SEM). The data analysis for the outer model involved validity and reliability testing, while for the inner model, various techniques such as the coefficient of determination (R-Squares), multicollinearity test, and hypothesis testing were utilized. The findings indicate a significant positive impact of both financial knowledge and FOMO on consumer behavior. Additionally, it was observed that financial knowledge has a notable positive effect on the Fear of Missing Out (FOMO).